SIMULATION OF PERFORATED BUCKET IN UREA PRILLING PROCESS - ,, MUHAMMAD AADIL (2014)
The dynamics of liquid droplets emanating from the orifice of perforated prilling bucket are of great interest to the industries which are using prilling process to manufacture the product in the form of spherical particles. In this process, liquid melt is sprayed by a perforated bucket to produce the droplets, which falls freely through a cooling medium and crystallized into spherical solid prills. Spraying of liquid melt is done by perforated rotating bucket which is installed at the top of the prilling tower. When perforated bucket is rotated at high speed, liquid jets are formed which breaks intcuiroplets-^dif&rent^zes^T4ie^%reateir^ impoTtancetrr" prilling process, as the size of the final product depends on the size of the droplets. The velocity of the liquid jets emanating from the orifice is important parameter in prilling process.